Implementation of the Project to Strengthen the Profile of Pancasila Students (P5) to Grow the Entrepreneurial - Harlina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This Research aims to Determine the Effect of Implementing the Project for Strengthening the Profile of Pancasila Student Entrepreneurship Themes in Fostering Students’ Entrepreneurial Spirit. Effect of Implementation The Problem Study Is The Extent To Which The Project Strengthens The Pancasila Student Profile And Fosters Students’ Entrepreneurial Spirit. This Research Examines The Project For Strengthening The Pancasila Student Profile, The Entrepreneurship Project For The Growth Of The Entrepreneurial Spirit, The Method Used Is Qualitative With Literature And Literature Studies, Theoretically And Empirically Analyzing The Growth Of The Entrepreneurial Spirit. This Research Also Explains Theoretical Measuring Factors For Further Research And Describes, Explains, And Measures The Growth Of Entrepreneurial Spirit Based On Theoretical Studies.